The Role of Environment and Space in the Reggio Emilia approach a Group-analytic interpretation - Mineo, Roberta (Rethinking childhood II: child and space, 2026)
The theme of educational spaces raises a fundamental question: is the environment only one part of the educational process or is it like a neural network, going through the whole body of education? In 1916, Dewey had laid the groundwork for one of the pillars of the Reggio Emilia Approach (REA): individuals seldom exist in isolation; instead, they usually interact with the objects and entities around them. Thus, the environment may be regarded as a space or a field in which networks of relationships, interconnections, and interactions between entities occur. In 1975, Foulkes defined space as a symbolic setting in which archetypes come to life, both in connection with the foundation and the dynamic matrices. As it embraces a progressive vision of education in seeking new kinds of schools for young children, Reggio Emilia is an inspirational early-years type of approach. It is not an educational model in the formal sense, with defined methods, teacher certification standards, and accreditation processes. In the Reggio Emilia Approach (REA), attention to the relatedness of spaces and environments implicitly defines the roles of pre-schools and their activities. The REA school is a group environment, based on participation and community management, collegiality and conviviality, and shared values and objectives. Creative spaces such as the atelier and the focus on the ecology of the environment are paramount to understanding the success of the REA educational approach. Group analysis and its concepts of the transpersonal and the matrix can shed new light on understanding the success of such educational approach, in terms of analyses of its historical components, but also its vision towards building a future for the young generation. The key here is the focus on REA’s political nature, understood as the unconscious level that links its founder’s pedagogy to its capability to interpret education as a symbolic space of collective decision making, empowerment of children, and the construction of a shared learning community.